Indonesian Spelling for Village Officials in Donorojo Village, Magelang Regency - Alfi Syahidah Dyah Puspitasari; Arinda Oktariski Setyaningsih; Azizah Nur Imani; Desyntia Amanda Putri Handayani; Sunu Setiawan Utama; Kundharu Saddhono; Uwe Barroso (Pengabdian: Jurnal Abdimas, 2023)
Background. Letter writing in Indonesian is an important part of written communication, both in the context of official letters and everyday communication. However, there are still frequent errors in its use, especially in terms of the use of capital letters, spelling, and punctuation. These errors were also found in official letters issued by government agencies in Donorojo Village, Mertoyudan District, Magelang Regency. Based on these problems, the UNS MBKM grant team conducted outreach to Donorojo village government officials regarding the management of letter writing as an effort to enforce Law No. 24 of 2009, emphasized PP No. 57 of 2014, and Minister of Education and Culture Regulation No. 42 of 2018. Purpose. The purpose of this activity is to increase understanding of the use of EYD in government staff correspondence products in Donorojo village. Method. The method used is socialization and mentoring using presentation materials and interactive games. This activity is divided into three stages, namely preparation, implementation, and evaluation. The preparatory phase involved needs analysis, participatory approaches, and the development of socialization materials. The socialization was carried out by providing material and understanding about PUEBI. The evaluation stage is carried out through games involving standard and non-standard words. Results. The result of this activity is an increase in understanding of the use of Enhanced Spelling (EYD) in government staff correspondence products in Donorojo village. Conclusion. Governance of correspondence in government agencies is regulated in the law, in particular, Article 33 paragraph 1 which reads "Indonesian must be used in official communication in government and private work environments".